2013
DOI: 10.1017/s0022215113000261
|View full text |Cite
|
Sign up to set email alerts
|

Computer or not? Use of image guidance during endoscopic sinus surgery for chronic rhinosinusitis at St Paul's Hospital, Vancouver, and meta-analysis

Abstract: Our study offers some evidence that computer-assisted endoscopic sinus surgery may delay residual disease and reduce the requirement for revision surgery. Although this finding was not borne out in the meta-analysis, the majority of identified studies demonstrated a trend towards fewer revision procedures after computer-assisted endoscopic sinus surgery. This type of surgery may offer other advantages that are not easily measurable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…Due to significant overlap between the existing systematic reviews, only the most robust is contrasted for discussion . Dalgorf et al provided the most rigorous coverage of evidence; the authors included all studies identified by the other reviews, had the most well‐defined inclusion criteria in terms of population and outcomes data, and was the most up‐to‐date (up to September 2012) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to significant overlap between the existing systematic reviews, only the most robust is contrasted for discussion . Dalgorf et al provided the most rigorous coverage of evidence; the authors included all studies identified by the other reviews, had the most well‐defined inclusion criteria in terms of population and outcomes data, and was the most up‐to‐date (up to September 2012) .…”
Section: Discussionmentioning
confidence: 99%
“…The additional information provided by SAL is thought to reduce the risk of perioperative complications in ESS by increasing surgical accuracy . Whereas the technical accuracy of SAL systems and software are well established, the efficacy of these systems in terms of reducing perioperative morbidity and improving surgical outcomes in complex ESS procedures has not been clearly demonstrated in the literature . Although a recent systematic review and meta‐analysis identified a reduced likelihood of total and major complications in ESS when SAL is utilized, the inclusion criteria for the review were not limited by the surgical indication …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Continuing with this line of thought, a future revision procedure could potentially be avoided, 15 one in which anatomy would have been distorted and complication risk may have been heightened.…”
Section: Current Technology and Usementioning
confidence: 99%
“…The introduction of computer-assisted surgery has definitely assisted in addressing difficult and challenging areas during ESS 35 ; this should not, however, preclude our anatomical knowledge and attention to different variations. In fact, navigation systems are not universally available and, in many centers, are not currently part of the set up for routine cases.…”
mentioning
confidence: 99%